Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173770
|View full text |Cite
|
Sign up to set email alerts
|

The Perils of Confounding Factors

Abstract: The design of Fitts' historical reciprocal tapping experiment gravely confounds index of difficulty ID with target distance D: Summary statistics for the candidate Fitts model and a competing model may appear identical, and the validity of Fitts' model for some tasks can be legitimately questioned. We show that the contamination of ID by either target distance D or width W is due to the common practices of pooling and averaging data belonging to different distance-width (D,W) pairs for the same ID, and taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Generally, an extension is deemed to be "superior" when tested against other models when there is a better correlation. However, there are numerous disadvantages to merely using the (R 2 ), which is supported by current literature [17,26].…”
Section: Evaluation Approachesmentioning
confidence: 85%
“…Generally, an extension is deemed to be "superior" when tested against other models when there is a better correlation. However, there are numerous disadvantages to merely using the (R 2 ), which is supported by current literature [17,26].…”
Section: Evaluation Approachesmentioning
confidence: 85%
“…In practice, studies have routinely found gaze to perform in accordance with Fitts' Law [26,41]. Researchers have suggested that these results are due to secondary corrective saccades when targets are small [51], or artefacts of experimental conditions or analysis methodology [21]. For this work, it also has to be noted that gaze is not always performed by the eyes alone.…”
Section: Pointing With Head and Gazementioning
confidence: 98%
“…Whether gaze pointing is appropriately modelled by Fitts Law has become a matter of considerable debate [11,21,51]. Eye movement, unlike head and hand movement, is ballistic in nature.…”
Section: Pointing With Head and Gazementioning
confidence: 99%
See 1 more Smart Citation